KEANEKARAGAMAN SPESIES AVES ORDO CORACIIFORMES DI KAWASAN HUTAN CRU (Conservation Response Unit) SAMPOINIET ACEH JAYA - Tanwirul Anwar; Rizky Ahadi; Arif Sardi (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Ar-Raniry Banda Aceh, Indonesia, 2024)
Bird diversity in an area is one of the guidelines in the management of biological resources. Birds play an important role in controlling insect populations, helping with pollination and seed dispersal. This study aims to identify the types of birds in the order Coraciiformes and identify their level of diversity in the CRU Sampoiniet forest area, Aceh Jaya. The method used in this study is the Point Count method with 10 observation points for each point. Then it is calculated with a duration of 15 minutes with a radius of 50 meters and a distance of 200 meters for each point. Data analysis used a bird species identification book and used the Shannon Winner diversity formula Ĥ = ∑ Pi Ln Pi. The results of the research on the diversity of species of aves the order Coraciiformes in the CRU (Conservation Response Unit) Forest Area of ​​Sampoiniet Aceh Jaya, consisted of 7 species from 3 families with a total of 33 individuals. The overall diversity index of species of aves of the order Coraciiformes Ĥ=1,89218, so the species diversity of aves of the order Coraciiformes in the Sampoiniet Aceh Jaya CRU (Conservation Response Unit) Forest Area categorized in the low diversity index.